Keratoconus: Diagnosis and Staging. Issue 1 (8th January 2022) - Belin, Michael W.; Jang, Hyun Soo; Borgstrom, Mark
Abstract: The advent of refractive surgery and corneal cross-linking for ectatic disease has further highlighted the need to recognize early or subclinical ectatic disease. Historical systems depend on anterior corneal changes that occur late in the disease course and are commonly associated with visual loss. Tomographic imaging allows for the acquisition of posterior corneal surface data and corneal thickness distribution. This led to the development of modalities to diagnose early or subclinical keratoconus and to screen patients for refractive surgery. This article reviews the modern methods for assessing changes in posterior corneal surface and pachymetric distribution, now accepted by the major cornea societies to be the hallmarks of ectatic disease. Screening tools utilized by the commonly used tomographic imaging devices are discussed, and the difference between screening for ectasia and diagnosing keratoconus is highlighted. The Belin ABCD staging and classification system and the ABCD Progression Display are reviewed as a new grading and monitoring system that can be used for earlier intervention and prevention of visual loss in keratoconus.